2020
DOI: 10.1186/s12879-019-4710-z
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal resistance in patients with Candidaemia: a retrospective cohort study

Abstract: Background: Candidaemia is the most common form of invasive candidiasis. Resistant Candida blood stream infection (BSI) is rising, with limitations on the development of broader-spectrum antifungal agents worldwide. Our study aimed to identify the occurrence of antifungal-resistant candidaemia and the distribution of these species, determine the risk factors associated with antifungal resistance and evaluate the association of antifungalresistant candidaemia with the length of intensive care unit (ICU) and hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
3
36
1
4
Order By: Relevance
“…The rate of fluconazole resistance against C. parapsilosis candidemia in our study was higher (59.1%) than those of previously reported studies (2–6%) [ 28 30 ]. Recently, the emergence of fluconazole resistance of C. parapsilosis from intensive care units (30–75%) has been reported [ 31 33 ]. The possible mechanism of fluconazole resistance may include genetic mutation (e.g., mutation of the ERG11 gene) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of fluconazole resistance against C. parapsilosis candidemia in our study was higher (59.1%) than those of previously reported studies (2–6%) [ 28 30 ]. Recently, the emergence of fluconazole resistance of C. parapsilosis from intensive care units (30–75%) has been reported [ 31 33 ]. The possible mechanism of fluconazole resistance may include genetic mutation (e.g., mutation of the ERG11 gene) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of fluconazole resistance may include genetic mutation (e.g., mutation of the ERG11 gene) [ 34 , 35 ]. Also, certain clinical factors such as previous exposure of antifungal agents, ventilation, and transfusion have been associated with fluconazole resistance of C. parapsilosis candidemia [ 31 ]. Moreover, a widespread mutation of the ERG11 gene was reported in fluconazole-resistant C. parapsilosis bloodstream isolates from a multicenter study in the Republic of Korea [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Candida glabrata is the second leading cause of candidaemia in USA, 1 Canada, 2 Australia 3 and some Scandinavian countries 4‐9 and the first cause of candidaemia in intensive care units and patients with haematological malignancies and solid tumours 10,11 . Compared to the other Candida species, C glabrata is much more tolerant to antifungals, 12 which allows it to rapidly develop antifungal resistance during the course of antifungal therapy 13‐22 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies reported results mainly for the following species: C. krusei , C. parapsilosis , C. glabrata , C. tropicalis , and C. utilis. These species are often selected because they are associated with infectious processes in humans and have virulence factors associated with greater disease severity [ 35 37 ]. Stratification of the results by the type of strain contributes to a better understanding of such results and to the establishment of breakpoints considering the diversity of findings for different situations.…”
Section: Discussionmentioning
confidence: 99%